IoT-Based Application Design for Battery Discharge Condition With C-Rate Variation - Saputra, Riza Hadi; Giyantara, Andhika; Dewanto, Muhammad Ridho; Sawung, Jheskia Ardito (Faculty of Engineering, Universitas Tanjungpura, 2025)
Lithium-ion (Li-ion) batteries are one of the most widely used energy storage technologies due to their advantages in high energy density, fast rechargeability, and efficiency. However, behind these advantages lie the weaknesses of lithium-ion batteries, namely that their performance and lifespan are greatly influenced by factors such as C-rate and lithium-ion battery temperature. A high C-rate can increase temperature and accelerate battery degradation, while a low C-rate tends to result in lower temperatures and more optimal capacity. This study aims to design an Internet of Things (IoT)-based State of Charge (SoC) monitoring system capable of real-time battery condition monitoring. The system uses an ESP32 microcontroller connected to a voltage sensor, an ACS712 current sensor, and an LM35 temperature sensor. The collected data is sent to Firebase and displayed through an Android application based on MIT App Inventor. The study focused on discharge cycles with varying C-rates: 1C, C/2, C/5, C/10, and C/20. SoC estimation was performed using the coulomb counting method. The results showed that as the C-rate decreases, the obtained capacity tends to increase, even exceeding the nominal capacity at C/20. Accuracy evaluation using RMSE yielded error values ranging from 0.12% to 4.04%. This system can serve as an effective solution for IoT-based battery monitoring